UPAYA REVITALISASI KORIDOR HEERENSTRAAT (LET.JEND. SUPRAPTO) DI KAWASAN KOTA LAMA SEMARANG - Yudawati, Rr. Adetia (VITASPHERE, 2012)
Revitalization is a process to revive cultural heritage about BCB (The historic object which protected by government) and KCB (cultural area which is protected by government) now and in the fUture. The main revitalization goal is, efforts to get the benefit from the revitalization that has purpose to increase their better life quality, good circumstance such as what lre have done to heererutaat corridor in kota lama area set as tourisms & cultural destination which isfamous in many countries. Those sites is a KCB (cultural area which is protected by government) & a historical building during Dutch period which we keep because having a high historical value. The activity to revive of Heererutraat Corridor was balanced by the activity to conservation of cultural building because the building is a ocular proof of culture work in the past which is a histories knowledge, history anthropology, archeology, the knowledge of architecture evolution. economic and tourist development